1998
DOI: 10.1046/j.1523-1747.1998.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coherent Near Infrared Radiation Protects Normal Human Dermal Fibroblasts from Solar Ultraviolet Toxicity

Abstract: The sun is the most important and universal source of non-ionizing radiation shed on human populations. Life evolved on Earth bathed by this radiation. Solar UV damages cells, leading to deleterious conditions such as photoaging and carcinogenesis in human skin. During the process of evolution, the cells selected dark- and light-dependent repair mechanisms as a defence against these hazardous effects. This study describes the induction by non-coherent infrared radiation (700-2000 nm), in the absence of rising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 26 publications
9
80
0
5
Order By: Relevance
“…If the UV radiation can have damaging effects upon human cells, and the redto-IR-A part of solar spectrum can have stimulating effects, then what could be the summary effects on the human skin? Menezes and coworkers (19) have suggested that preirradiation with IR light (e.g., during sunrise) is a natural process whereby cells are protected against the solar UV radiation, which was acquired and preserved through evolutional selection and plays an important role in life support. They found that visible-tonear-IR radiation at 400-2000 nm protected human dermal fibroblasts from UV-A and UV-B cytotoxity (19).…”
Section: Radiation In Red and Ir-a Region Is Protective Against Harmfmentioning
confidence: 99%
See 1 more Smart Citation
“…If the UV radiation can have damaging effects upon human cells, and the redto-IR-A part of solar spectrum can have stimulating effects, then what could be the summary effects on the human skin? Menezes and coworkers (19) have suggested that preirradiation with IR light (e.g., during sunrise) is a natural process whereby cells are protected against the solar UV radiation, which was acquired and preserved through evolutional selection and plays an important role in life support. They found that visible-tonear-IR radiation at 400-2000 nm protected human dermal fibroblasts from UV-A and UV-B cytotoxity (19).…”
Section: Radiation In Red and Ir-a Region Is Protective Against Harmfmentioning
confidence: 99%
“…Menezes and coworkers (19) have suggested that preirradiation with IR light (e.g., during sunrise) is a natural process whereby cells are protected against the solar UV radiation, which was acquired and preserved through evolutional selection and plays an important role in life support. They found that visible-tonear-IR radiation at 400-2000 nm protected human dermal fibroblasts from UV-A and UV-B cytotoxity (19). It was also found in this work that the protection was independent of the (20).…”
Section: Radiation In Red and Ir-a Region Is Protective Against Harmfmentioning
confidence: 99%
“…The dermis tends to increase the amount of fluid by inducing an increase in collagen, elastin, and water-binding protein in order to protect subcutaneous tissues from NIR (Tanaka et al 2009a(Tanaka et al , 2009b. Pre-exposure of NIR prevents UV-induced toxicity (Danno K et al, 1992;Frank et al, 2004;Menezes et al, 1998), and this effect is independent of heat shock protein induction and cell division (Menezes et al, 1998). These findings suggest that NIR irradiation prepares skin to better resist the subsequent damage of UV or NIR.…”
Section: The Effects Of Nir On Human Skinmentioning
confidence: 80%
“…Overall, these results, although observed in a small sample of subjects, suggest that a state of cellular resistance to UV insults was induced following LED photoprophylaxis. It can be hypothesized that this cellular resistance may be achieved experimentally by triggering/stimulating an existing natural protection mechanism [3]. In effect, in the natural environment, visible and IR solar wavelengths predominate in the morning and UV-B and UV-A are predominant around noon.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Menezes et al [3], it was demonstrated that a narrow electromagnetic spectrum window IR wavelengths (700-2,000 nm) generated a strong cellular defense against solar UV cytotoxicity in the absence of rising skin temperature. In a follow-up to this study by Frank et al [4], it was proposed that IR irradiation prepares cells to resist UV-B-induced damage by affecting the mitochondrial apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%